Arabiens arkæologi - Bibby, Geoffrey (Kuml, 1964)
Arabian Gulf archeology The Eighth Campaign of the Danish Archeological Expedition 1961/62 During the winter of 1961/62 the expedition sent out from the Forhistorisk Museum in Aarhus continued its work on the Arabian littoral of the Arabian Gulf, operating in Bahrain, Qatar, Kuwait and Abu Dhabi. The expedition, which was in the field from 17th October 1961 to 29th January 1962, was under the leadership of Professor P. V. Glob, with T. G. Bibby as deputy director. There were 26 participants. As in previous years generous grants were received from a number of supporters in Denmark and the Arabian Gulf, including the governments of Bahrain, Qatar and Kuwait, the Bahrain Petroleum Company, the Qatar Petroleum Company, the Abu Dhabi Petroleum Company and the Carlsberg Foundation. The report on the work in Kuwait during the campaign will be published in Kuml 1965. Bahrain In Bahrain work was concentrated on the two sites already extensively investigated during the previous seven campaigns, the third-millennium temple-complex at Barbar and the city-mound at Qala’at al-Bahrain, while investigations were also made of two of the large burial mounds south of the village of Ali. Barbar. Here Hellmuth Andersen and Peder Mortensen completed their investigation of the temple-complex with a series of excavations on the outskirts of the site: To the west of the temple two trenches dug E-W revealed, at a depth below that of the original temple, two building phases with remains of houses built in unworked stone set in clay, the walls in some cases plastered with gypsum. The lower building level was contemporary with Temple II or early Temple III, the upper level with late Temple III. The excavation was extended to uncover some rooms of a house belonging to the earlier phase, while a seal was discovered below a floor belonging to the later phase. North of the temple the outer terrace wall of Temple III proved to be poorly preserved, in one to two courses of stone. It was, however, thereby shown that the temple had been completely surrounded by an oval terrace wall, in the same way as the temples of Khafaja and al-’Ubaid in Iraq. South and east of the temple trenches were dug down to the original ground surface, revealing remains of buildings contemporary with Temple I below a thick burnt layer south of the "temple oval" (Mortensen, KUML 1956). Supplementary excavations were made below the stairways and altars of all three temples, and along the lines of the draining channels belonging to Temples II and III, the latter investigation producing half an alabaster macehead from a Temple III level. In addition two trenches were dug southward and eastward from the house site to the northeast of the temple (Harald Andersen, KUML 1956). These showed that this house had originally stood on a walled terrace, 1.5-2.0 meters high. The terrace wall had later been quarried away, but its course could be identified in the sections, while some of the large cut-limestone blocks of the wall still lay along the edge of the quarry trench. At the conclusion of the work the flagged floor of Temple III, together with the large circular plinths and the three perforated stones (Glob, KUML 1954 & 1955), which had been removed to facilitate investigation of Temples I and II, were replaced in position, and the whole site thereafter covered in again by bulldozer. This step was necessary, as much of the stonework of the later temples had been considerably undercut during investigation of the earlier levels, and if these walls had been left exposed weathering of the sand on which they stood would have quickly resulted in their collapse. The covering with sand is thus a temporary safety measure until such time as adequate plans for restoration and preservation of this unique ancient monument can be agreed upon. (The above based on a report by Peder Mortensen). Qala’at al-Bahrain. In the already excavated portion of the large "palace" building Hans Berg and Karen Frifelt dug a series of section trenches at right-angles to the walls in order to reach a more trustworthy dating of the building (which has proved tantalizingly difficult to date owing to a complete lack of any "occupation-stratum"). In the course of this work an area of the floor of the large entrance hall was taken up and a number of "snake-offerings" (Glob, KUML 1957) discovered. Most of these lay in small pottery bowls covered by a potsherd, while one lay in an alabaster bowl and several had no container, being merely covered by a potsherd. In the "throne-room" (Glob, KUML 1959) -more probably a chapel- an E-W section trench was dug in connection with the "throne" and a drainage basin was discovered in front of it, below the cement floor. The basin was built up of unshaped stones and pieces of cement and was covered with 4 limestone slabs. The "throne" was removed and the floor and soil beneath investigated without result. To the east of this area the rooms of the "palace" building were removed. Below them portions of two large buildings of the Kassite period ("caramel-ware" period -Bibby, KUML 1957) were discovered with a narrow alley between. Portions of drains covered by stone and cement slabs were excavated outside these buildings; the drains were interrupted by the foundations of the Kassite buildings and must therefore be older than these. The southern Kassite building had consisted of a central court running E-W and probably roofed, with rooms on either side. South of the court one room was excavated completely and two partially. They had all been destroyed by an extensive fire, and here were found potsherds, remains of bronze and corn, and the impress of wood. Above the burnt layer, in a level characterized by quantities of collapsed masonry, but below the cement floor of the "palace" building (in which no break was noted) lay a pottery vessel containing a quantity of silver and remains of woven cloth. This silver board (fig. 1) consisted of pieces of smelted silver, portions of bracelets clipped into several pieces, and a number of complete rings and earrings. Conspicuous among the ornaments was a signet ring bearing Egyptian hieroglyphs (fig. 2). This has been dated (by the National Museum, Copenhagen) to 650-550 BC. The hoard was apparently the stock of a silversmith buried in the ruins of the Kassite building. Its bearing on the date of the "palace" depends on whether it was buried before the construction of this building or below (and therefore through) its floor. Though no break in the floor was observed attention was not of cource particularly directed to the spot at which the hoard was later to be found. ’ North of the court of the Kassite building two rooms were excavated completely and one partially. The westernmost of these rooms had a floor raised above the general level and approached by two steps in the full width of the room. In the centre room a burnt level just above the floor consisted of a thick layer of bitumen mixed with potsherds and the impress of wood, and in addition of a large heap of burnt date-stones. Just above this burnt level was found a fragment of a cuneiform tablet (the first clay tablet to be found in Bahrain), two bronze spearheads and a bronze hoe-blade. A sample taken from the burnt date-stones in this room has been subjected to C 14 analysis, which has given a result of 1180 ± 110 BC (K-827). (The above based on a report by Karen Frifelt). Work was also continued on the western fortification wall of the city, where Aino Mortensen and Elsebeth Sander-Jørgensen made a section through the wall and the area within, while Geoffrey Bibby and Jytte Thomsen traced the southward course of the wall. The section demonstrated conclusively that the wall was constructed on bedrock during the Barbar period and extensively rebuilt in Kassite times, at which period the wall was broadened by the construction of a parapet on the inner side of the wall. This confirmed the findings of the previous year, as well as the conclusion that the wall was given up and already underground by the Seleucid period, at which time a number of two-roomed houses were built on the edge of the slope above it. No trace was found of occupation within the wall at the time when it was in use. The wall was found to continue due south in a straight line for at least a further hundred meters, and at this final point reached a small portal was found in the wall. The portal was at "parapet" level, 1.75 meters wide and 2.6 meters above the base of the wall. The wall had at this point been strengthened by a bastion, based like the wall on bedrock, keyed into the wall and projecting some 75 cms. out from it. This suggests strongly that there may have been a ditch outside the wall, bridged at this point by some wooden construction. Ali. Investigations were carried out by P. V. Glob of two of the huge burial tumuli at Ali which had been dug into to a considerable depth around the edges by quarrying bulldozers. In both cases the bulldozers had exposed, and partly removed, a circular ring-wall which had, as far as could be seen, stood to a height of approximately 3 meters, some meters in from the foot of the mounds. In both cases it proved possible to locate an entrance passage running from a gap in this ring-wall radially inward towards a central chamber. The passage way, about 2 meters wide, was lined with dry-stone walls of quarried limestone blocks to the same height as the ring-walls at the outer end and increasing gradually to about 4 meters. There was no roof. In both cases the passage was excavated in a length of about 14 meters as far as the central chamber (the last 2.5 meters of one of the passages being plastered), and in both cases it was found that the roof blocks of the chamber had broken and fallen in, being supported only by the sand which had filled the chambers. It proved impossible to obtain tackle of a strength necessary to support these stabs, several tons in weight, during an excavation of the chambers, and both excavations had to be abandoned at this point. In both cases it could moreover be seen that robber-tunnels had previously been dug through the entrance passages. In one case a trail of potsherds, scattered by the robbers in their tunnel, could be assembled to form a nest of three small bowls and two "wineglass" -shaped beakers with painted geometric ornamentation in black on a red slip (fig. 3). In addition to the expedition members mentioned above Vibeke Kristensen took part as draughtswoman and Vibeke Bibby as commissariat supervisor. Qatar In Qatar the survey of flint sites was continued by Holger Kapel, assisted by Hans Jørgen Madsen and Jens Aarup Jensen. It was concentrated mainly in the north and northeast of the peninsula, where ten sites characterized by large implements of primitive character were found near Khor, while further work was done around Dukhan on the west coast. (The results of the whole course of Stone-Age research in Qatar are summarised in this issue, p. 112). A very considerable area of rock-carvings was discovered at Jebel Jasasiyah in the northeast of Qatar. Here smooth rock outcrops slope in the main downwards towards the east, though carvings are also found where the slabs are horizontal or westward sloping. The most common pattern is in the form of a double row of cupmarks, while another frequent design is a rosette, a ring of cupmarks with often a larger hollow in the centre. Large holes, some the size of a bathtub, have also been cut into the rock. In addition there are carvings of ships, viewed from above, with oars, steering oars, and bow and stern platforms (fig. 4), and in one case with an anchor rope and anchor. The field of carvings was extensively mapped, sketched and photographed. A number of excavations of burial mounds was carried out during the season by H. J. Madsen and J. Aarup Jensen. Investigations of ten small cairns in a tumulus field of about a hundred at Ras Abaruk gave little result, as the graves had been extensively disturbed. Only in three cases was a stone-lined chamber traceable, and apart from 26 beads from one chamber and 82 from another there were no significent finds in the graves. One rim sherd, however, found in a scattering of potsherds round one of the cairns, suggests strongly an early Seleucid date, around 300 BC. More interesting were the results obtained from Mezru’ah, south of Khor, where lay two large and two small tumuli. One large and one small tumulus were excavated. The large tumulus, measuring about 1.5 meters in height and 15 meters in diameter, covered three graves, all dug down about 20-30 cms. through a thin brown humus-like stripe marking the original ground surface and all covered with a built-up mound of stones. The central and largest grave had been plundered, and only fragments of human bones, bronze, iron, glass and potsherds were found. The two peripheral graves, with a smaller coverage of stones, contained the skeletons of camels, apparently in a kneeling position, while one grave also contained a glass flask. The small tumulus, about 0.5 meters high and 6 meters in diameter, covered an irregular grave dug through the original surface humus level and covered with three large slabs of stone. It contained two human skeletons in very contorted positions. An iron sword and a bunch of iron arrowheads were found in the grave, while an arrowhead was found by the groin of one skeleton and another embedded in the bone of the left lower arm. In addition at Ras al-Matbakh, on the northeast coast, a large jar was investigated, lying just under the present surface level about 35 meters from the shoreline. The jar lay on its side with a stone setting around its mouth, which pointed due south. The whole site had been badly disturbed very recently, and the jar contained recent animal bones and paper, but at the bottom lay a human skeleton apparently originally in a contracted position with its head to the south. (The above based on reports by Hans Jørgen Madsen). Abu Dhabi In Abu Dhabi a team consisting of Knud and Lise Thorvildsen, Arne Thorsteinsson and Vagn Kolstrup continued the investigation of the burial tumuli of the island of Umm an-Nar. The results of this investigation have already been published (Thorvildsen, KUML 1962). Towards the end of the season the team moved to Buraimi, a hundred miles inland on the western edge of the Oman mountains, and spent a fortnight investigating the tumuli already discovered there (Glob, KUML 1959). Five mounds were excavated and proved to be of a completely different structure from the round sepulchral buildings of Umm an-Nar. They consisted of cairns of stones built up around a central corbelled chamber approached by a narrow entrance passage through the thickness of the mound, a length of up to 2 meters. The graves appeared to have been plundered, but two large bronze pins were found, together with fragments of steatite bowls and two complete pottery vessels. These latter were completely different from those of Umm an-Nar, being small roundbodied vases of biscuit-colored ware with flat collar-rims. No conclusions could at this stage be drawn concerning the date of these tumuli. The Ninth Campaign of the Danish Archeo/ogical Expedition 1962/63 From 4th November 1962 the Danish Archeological Expedition to the Arabian Gulf was once again in operation in Bahrain, Qatar, Kuwait and Abu Dhabi, work continuing until 16th February 1963. In addition, by the good offices of the Arabian-American Oil Company, it proved possible for the first time to carry out a reconnaissance of the nearer portions of Saudi Arabia. The expedition was, as usual, under the directorship of Professor P. V. Glob, with T. G. Bibby as deputy director. There were 25 participants. The expedition wishes once more to record its gratitude to the numerous supporters of its work, including the governments of Bahrain, Qatar and Kuwait, the oil companies of Bahrain, Qatar and Abu Dhabi, and the Carlsberg Foundation. Bahrain Work during this season was concentrated upon two projects: the "tell" of Qala’at al-Bahrain, where a further area in the centre of the mound extended our knowledge of the "palace" building and the Kassite buildings below and where sondages were made along the expected line of the south defensive wall of the city; and the tumulus fields south of Ali, where -following the excavations last year in two of the largest mounds- over forty of the smaller tumuli were investigated. In addition to the excavators mentioned in the body of the report Malene Møller-Jensen took part as draughtswoman and Vibeke Bibby as commissariat supervisor. Qala’at al-Bahrain. In the central area Karen Frifelt and Hans Chr. Vorting extended the previous years’ excavations a further 5.5 meters towards the east in a width of 20 meters, and the upper layers of earth were removed down to the level of the "palace" building. In these layers remains of Islamic buildings were found, comprising an Islamic well which was cleaned out down to Kassite levels, some remains of walls and floors, and several of the so-called ovens. A large part of the area, however, had been disturbed by earlier pits which had thereafter been refilled with rubbish including an unusual number of potsherds. Among the objects discovered was moreover a "tripod" spacer of the type used during the firing of pottery, which would suggest that there had been a potter’s workshop in the vicinity. Among the rubbish layers were found fragments of small animal figurines and two imported Greek sherds. Standing at floor level of the "palace" a few meters apart were two burials in pottery vessels. No traces could be seen of these burials having been dug down from a higher level, but this would in any case have been difficult to see in the rubble. The one consisted of a thick oval jar of red clay which was found on excavation to have been broken and to be full of earth. However, there were found in it some badly preserved bones, two teeth, a fragment of a bone amulet with a five-pointed star on one side and three parallel lines on the other, and a fragment of a blue glass bead. The other burial was an infant inhumation in a bowl-shaped vessel of reddish yellow clay. Though no lid was preserved the burial was undisturbed, an infant lying curled up, with legs drawn up, head to the south and face turned towards the west. There were no objects with the skeleton. A further series of rooms were excavated in the complex of buildings associated with the "palace" with its great wall. The largest of these rooms measured over 10 meters in length by 4.5 meters in width, and had, in either sidewall, opposite one another, an imposing double door, of which only the threshold stones and the fine semicircular carved hinge-stones on either side of the thresholds now remain. There were also doorways in the end walls of this room, and the remains of a hearth were found at each end. The walls of the other rooms were almost entirely demolished, in some cases well into foundation level. Towards the south of the excavated area a stretch of cobbles was presumably the remains of an E-W-running street. After all the remains of buildings had been planned and measured they were removed, and the levels below excavated down to the level of the Kassite buildings. These levels consisted of "fill" containing much stone and rubble and few potsherds. Here was found a fragment of clay with a portion of a seal impression, probably of a cylinder seal. A further two rooms were excavated within the massive Kassite building (with walls up to a meter thick) which was discovered the previous season, as well as a portion of the covered court. Here too traces were found of a fierce conflagration, and in the burnt layer the impress of wood and of woven palm-mats, possibly from the roof. In one of the rooms a "bathtub"-coffin burial of later date was found. The thick plaster floor had been pierced, and the coffin stood N-S with its upper edge about 40 cms. above floor level. It was thus without a doubt later in date than the Kassite building. In spacial relation to the "palace" building above it lay just within the threshold of the southern double door in the room described above, and of course a considerable distance below its floor level. The floor at precisely that point had been described, before the burial was discovered, as "uneven and partly worn away", and had been drawn as a broken patch. It seems probable, therefore, that the "bathtub"-coffin had also been buried through this floor, and is therefore of later date than the "palace". To judge by impressions remaining the coffin had had a wooden lid and been sealed with bitumen. The burial was undisturbed, and the coffin contained a skeleton in poor condition, on its side with head to the south facing east and with arms and legs drawn up under the chin. The only burial gift was a vase by the head. In the northern part of the excavation area a continuation of the narrow alley found the previous year proved to contain a large number of hammer stones, while on the northern side of the alley the outer walls of the second Kassite building continued. (The above based on a report by Karen Frifelt). Along the southern edge of the "tell" Kirsten Kassow and Mogens Bencard carried out a series of excavations in order to discover the nature and location of the defensive wall of the city in this area, following its investigation in previous years in the north and west of the city. The excavations in the southwest area were complicated by the presence of very massive walls of Islamic date following closely the original line of the "Barbar-period" wall. However, close to the present-day village on the site it proved possible to uncover a portion of the wall completely, and it was shown to agree closely in construction with the west wall of the city, like it (and unlike the north wall) being built directly upon bedrock. A little further to the east, immediately south of the "palace" excavation, a 1.5 meterthick Islamic wall was found resting directly upon the top of a curtain wall surmounting the Barbar-period fortification wall. Incredible as it appears, the conclusion seems inescapable that here the original fortification wall is preserved in its full height to the very tip of the parapet wall. The curtain wall, 30 cms. thick and 1.3 meters high, was built on the outer, southern edge of the fortification wall, which itself stood at this point to a height of 3 meters, founded upon bedrock. The outer face was plastered, and thus presented a sheer smooth face, 4.3 meters from top to bottom. The thickness of the actual fortification wall could not be determined, as the whole of the rear of the wall had been quarried away in its full depth. The surviving maximum thickness was a little over a meter. In general the area inside the wall showed signs of considerable disturbance at many periods, and only an extension of the excavation to cover a considerably larger area would be able to unravel the history of the wall at this point. In particular an explanation is lacking for the presence, in the "Barbar" levels within the walls, of portions of the dismembered and partly burnt skeletons of at least eight human beings. A final sondage was made some 300 meters further to the east, on the southeastern edge of the "tell" and far from any area which we have previously investigated. Here the Barbar-period wall was not located, and the presence of Barbar-period occupation levels and house walls just above bedrock at a depth of 7-8 meters suggests that the edge of the Barbar-period city lies further to the south. However, a wall with a thickness of 2 meters, slightly sloping sides and a "glacis" 1 meter broad at the foot of the outer face was discovered at this point and proved to be dateable to the Kassite period, which was particularly richly represented in occupation levels at this point. Two burials of this period were also found here; they were simple contracted inhumations, lying on the left side and facing north. A little glazed vessel was found with one of the skeletons. Tumuli south of Ali. A study was made during this season by P. V. Glob, Peter Crabb and Grith Lerche of burial mounds in the tumulus field south of Ali, a field which had been considerably damaged by bulldozing for gravel. The action of the gravel-diggers had frequently exposed the chamber of a mound, and it was thus possible to excavate, draw and list the contents of fortytwo mounds, even though the outer construction of the mound had in almost every case been destroyed. Every chamber had been anciently opened and plundered, and nothing of great intrinsic value was therefore found, except for one small gold link composed of four spirals radiating outward from a central point. Nor was any skeleton found in situ. But a considerable quantity of skeletal material was recovered, opening the possibility of statistical analysis, and confirming that in no case was there ever more than one burial in each chamber. A large amount of pottery was found, including sufficient of the typical red ridged "Barbar" ware to confirm the contemporaneity of the tumuli with the "Barbar period". The finds also included alabaster bowls and ostrich-egg beakers. It is noteworthy that there were none of the typical Barbar-period seals, but in two of the chambers "mock seals" were found, fossil seashells carved into the shape of a Barbar-type stamp seal, the natural spiral ridges of the shell forming the obverse of the seal. Two areas within the same mound-field were chosen for investigation, the first (16 mounds) immediately adjacent to the group of large tumuli south of Ali, and the second (26 mounds) about one kilometer further south and uphill. The difference between the two groups was striking: in the first group the chambers were larger, with cut limestone and regular coursing contrasting with the small chambers and rough unshaped stone of the second group. The contents of the chambers of the first group were also richer than those of the second. On the other hand the actual tumuli of the second group -in so far as they survived- were generally larger than those of the first. This was largely due to the fact that the chambers of the first group were partly (and sometimes almost wholly) below the original ground surface, though never cut down into the bedrock, whereas the chambers of the second group had been built upon the original ground surface, not only where the bedrock was close to the surface but also where, in a wadi, there was a considerable depth of earth. In these cases it could be seen that the layer on which the chambers were erected was of humus (see p. I 04, and Bibby, KUML 1954). During the course of this investigation an examination was made of a large low mound just south of the Ali road in which, as a result of quarrying, a number of plastered walls could be seen protuding, while Barbar-period sherds were found mixed with Islamic sherds in the debris of the quarrying. A section through one side of the mound was cleaned up and cleared back for about a meter to give an undisturbed stratification. This demonstrated clearly that the building with plastered walls, almost certainly a large house, was of Islamic date, but built above a settlement with unmixed Barbar-period sherds. Only one wall, however, could be ascribed to this earlier settlement. Qatar During this season the Stone-Age survey of Qatar -described elsewhere in the issue, p. 148- was continued by Holger Kapel, Svend Bue-Madsen and Erik Bendixen, while the two latter also carried out the excavation of a settlement site of Seleucid date, found this year at Ras Uwainat Ali, immediately north of Dukhan on the west coast. The site was identified by a scattering of the typical potsherds of the period, the thin bowls (Bibby, KUML 1957) of buff and of red or black burnished ware, on the surface of a low hillock of sand. Though sections were dug through this hillock in two directions and down to bedrock no signs of any permanent construction were found. But nearly 800 sherds, comprising portions of at least 75 vessels, were recovered from the upper levels of the sand. Apart from the flint sites no settlement of pre-Islamic date had previously been found in Qatar, and it is clear from the objects found here that settlements of this nature must have been rare. For the thin bowls, of types used and discarded in their hundreds during the Seleucid period in Bahrain, had here been carefully repaired when they became broken, rows of holes being bored along the edge of the breaks to hold rivets or thongs. Abu Dhabi A team consisting of Jens Aarup Jensen, Vagn Kolstrup and Jørgen Lund spent a month excavating in the settlement immediately to the east of the gravemounds on the island of Umm an-Nar, before proceeding to Buraimi in the interior, where they spent a fortnight excavating the gravemounds south of Al-Ain. Umm an-Nar. Excavation here commenced at a point on the southern outskirts of the settlement mound where the walls of what was apparently a single-roomed stone but could be seen on the surface. It soon became clear that the walls visible on the surface were only part of a much larger building, and by the end of the season 300 square meters of a large house had been excavated without the end being reached. The part excavated is almost square, measuring about 16 X 16 meters. It continues to the northeast, but has outer walls on the other three sides. Its interior is divided into seven rectangular rooms, all about 3 meters wide and up to 11 meters long (fig. 5). The house was built on a fairly level rock surface, which, however, slopes slightly towards the shore, so that the east corner is about a meter lower than the west. The walls are about 90 cms. thick and preserved to a height of 80-90 cms., being about 8 courses of the flat blocks of local limestone. Clay was used as mortar, while at several points, particularly in two of the rooms, there were remains of clay plastering. Between the rooms there were doorways 80-95 cms. wide, three of them with recognizable hinge-holes. Although the upper levels excavated were full of fallen stones from the walls the quantity found is scarcely sufficient for more than a further 2-3 courses, so that, unless stone has at some later time been removed from the ruins, the upper part of the walls and the roof must have been of some lighter, more perishable material, wood, matting or palmleaves. In two of the rooms a single large pit had been dug, while in two other rooms smaller holes, probably postholes, had been cut in the bedrock, though in no recognisable pattern that could give valid evidence concerning roof construction. Potsherds formed the greater part of the objects discovered, and the majority of these were of thick-walled "kitchen-ware". However, the fine red ware with black painted decoration, which is known from the burial mounds of the island, was represented by some few sherds in almost every room, thus confirming that the settlement and the graves are contemporary. Sherds of this type were found mainly in the lower part of the occupation layer, but this is probably due to the fact that the surface of sherds in the upper levels had largely scaled off, destroying the painted decoration. A large quantity of bones was recovered, including the horns of goats and sheep, bones of fish and turtle, and the bones of a whale of a length of 2-3 meters. There were also the large leg-bones of camel, which strongly suggests that the camel was a domesticated animal in the Oman during the Third Millennium BC. Implements found suggest an economy largely based on fishing, comprising large numbers of net-sinkers of local limestone, 3 copper fish-hooks without barbs, 3 large curved copper needles, and various objects of horn and bone, including awls and a spindle-whorl. A small rubbing-quern and a number of stones not of local origin and more or less shaped which may be weights complete the inventory. The only ornaments found were two stone beads and a bone ring. There were no figurines, seals or inscriptions. Below the uppermost rubble layer there was, in almost every room, a conspicuous level of ash, and below this the occupation levels seemed to have accumulated slowly and without obvious interruptions. There was nothing to suggest a division into different "culture-periods". Various alterations and additions to the house had been made from time to time, walls being added and doors blocked up. All the rooms showed signs of having been living rooms, none having obviously had any special function as kitchen, storeroom or the like. (The above summarised from a report by Jens Aarup Jensen). Buraimi. During the course of the fortnight spent excavating at Buraimi twenty tumuli were investigated along the lower slopes of the two lines of cliffs which border the valley leading south from Al-’Ain to Jebel Hafit. The object of the investigation was to obtain so large a body of material objects from the mounds as possible, and mounds were therefore chosen which had been subject to recent stone-plundering and therefore required little excavation to reach the central chamber. All the mounds proved also to have been robbed in more ancient times, by robbers who had broken in through the top of the chamber. The result of this modern and ancient disturbance was that it was rarely possible to do more than draw the plan of the chamber and the entrance passage. A section was, however, successfully made through one of the mounds. They all proved to be of the same construction as those excavated in the centre of the valley in the 1961/62 season: cairns built up of loosely heaped local stone around a false dome over a round or slightly oval chamber, constructed upon the original ground surface and approached by a narrow entrance passage on the southern side. The original diameter of the cairns has been about 7-11 meters, and the original height 3-5 meters. The chambers measure, at floor level, about 2 meters at their greatest length, the largest found (cairn 22) being 2.85 X 2.6 meters and the smallest (cairn 19) 1.35 X 1.25 meters. The entrance passage, at ground level about 0.5 meters wide narrowing to 0.25-0.35 below the roofing slabs, was about 1.0-1.4 meters high and normally partly or completely blocked with stones in its full length. Cairns 10, 15 and 17 were completely empty, cairns 6, 18, 24 and 25 contained only scattered bone fragments. Of the remainder most contained a pottery vessel of the type found the previous season, flat-based, biconical, with a short cylindrical neck and a flat outturned collar-rim. In cairn 22 three vessels of this type were found, together with nearly 400 beads and a leaf-shaped bronze arrowhead, while in cairn 23 were two of the vessels, two bronze pins 11-12 cms. long and a bronze dagger blade of triangular shape measuring 21.5 X 6.3 cms. with a slight central rib and two rivets. The richest grave, however, was cairn 20, containing an ornamented steatite bowl, two bronze bowls, one with a spout, a large flat button of polished shell, a belt buckle of bronze and a short bronze sword, 42.5 cms. long (fig. 6). This sword, with a bronze hilt recessed to take an inlay and with a decoration of raised concentric circles at the junction of hilt and blade, has no exact parallels elsewhere in the Middle East. The closest resemblance, however, is seen in swords from Luristan [1] dating to the 13th and 14th centuries BC, suggesting a date within this range for the burial cairns of Buraimi. Little evidence concerning burial practice was found to have escaped the grave robbers, but in the rich cairn 20, where a roof collapse seems to have prevented complete plundering, some bones seemed to lie in a position suggesting that the body had been placed on its side with head to the east. The two bronze vessels and the steatite bowl lay by the head, probably nested within each other, the shell button by the hips. The sword lay with its point towards the skull, but may not belong to the same burial, as all chambers have room for several burials, and the remains of four different skulls were found in cairn 14. No cremated bones or charcoal were found in any chamber. A blade knife of flint was found in cairn 7 and an oval scraper close to cairn 20. After the completion of the excavating programme a number of reconnaissance trips were made within Abu Dhabi territory. These revealed that similar cairns, though some up to three times the size of the largest at Al-’Ain, were to be found along the eastern side of Jebel Hafit, though none were to be seen along the west side. To the east of the villages of Sa’ara and Hili several hundred cairns could be counted (at a distance as the border is uncertain) on the summit and slopes of Jebel Auha. A circle of stones protruding from the ground in the savannah southeast of the village of Hili, which had been discovered the previous season, was revisited and a large number of potsherds collected from within the ring. They were of Umm an-Nar type, and this site and a number of the neighbouring hillocks are probably the remains of Umm an-Nar-type burial chambers on a larger scale. (The above based largely on a report by Jens Aarup Jensen). Saudi Arabia During the period 4-9th December 1962 a short but intensive reconnaissance trip to Saudi Arabia was made by Vibeke and Geoffrey Bibby, as the guests of the Arabian-American Oil Company. On the morning after arrival an aerial reconnaissance was made, covering a tumulus field south of Dhahran airport, an area among the dunes further south along the coast where an extensive pattern of former irrigation ditches was to be seen, and the ruins of a walled city at Uqair still further south. The flight then went inland to the oasis of Hofuf, and from there north to Thaj where, surrounding a small modern village, there were the clear remains of a large walled city with, outside its walls, a number of large tumuli and of large disc-shaped mounds. The return flight to Dhahran was by way of a small water-hole called Ain as-Subaighawi where remains of buildings had been uncovered during road construction, Jawan where a cruciform tomb of Seleucid date had been excavated by Ric. Vidal of Aramco, and the island of Tarut north of Dhahran where a ruined fort crowned a conspicuous "tell" in the centre of the island. During the following days most of these sites were visited by motor vehicle, in every case guided by enthusiastic and knowledgeable amateur archeologists from Aramco. Ground reconnaissance was made at all sites visited and surface collections of potsherds made. At Thaj sherds of imported Greek black-on-red burnished ware were found, as well as fragments of clay figurines, and numerous sherds of the "thin bowl" type so well known from Qala’at al-Bahrain and the "Ikaros" settlement on Failaka. Gravestones with inscriptions in Nabatean script were seen built into the houses of the modem village [2], while a pot was found with a painted inscription in a more cursive script. At Ain as-Subaighawi and at Jawan numerous sherds of the "thin bowl" type were found. An attempt to reach the irrigation-ditch area north of Uqair proved unsuccessful as the vehicles met impassable dunes. At Uqair considerable time was spent examining the ruins of the walled city, which has frequently been suggested as the possible site of the city of Gerrha so often mentioned in the Classical writers [3]. The ruins, now largely drowned in sabkha (salt marsh), are built largely of coral and of the sea-bed conglomerate known locally as farush. The type of construction resembles that of Islamic times in Bahrain, and in no way resembles the Bahrain or Kuwait architecture of the Seleucid period; there was, for example, no cut limestone. The pottery was entirely of Islamic date, with not a single sherd of the "thin bowl" type found at three separate sites the day before. The conclusion must be that there is no surface evidence for an identification with Gerrha. A day was spent investigating a number of sites within the oasis of Hofuf. A large number of deserted settlements and "tells" produced only Islamic sherds and coins, while in the central area a small field of tumuli, already recorded by Ric. Vidal, was devoid of sherds or dating indications. Immediately south of this tumulus field, however, (about 1.5 kilometers out from Hofuf town on the track to Jebel Sha’ban) an immense tumulus, at least twice as big as the largest on Bahrain, was examined south of the road. It had been quarried from both sides so that only the central baulk remained, and large stones of what appeared to be a central chamber were clearly visible. No sherds or other indication of date were found. The tumulus field south of Dhahran airport resembled closely the tumulus fields of Bahrain, and on one of the mounds, which showed signs of having been dug into, three sherds of red ridged ware of Barbar type were found. There can therefore be little doubt that these mounds are of "Barbar" date and of the same type as those of Bahrain. Tarut was not visited, but a general reconnaissance tour was made over the desert inland from the coastal towns of Qatif and Dammam, where very large areas are covered with potsherds. Typical collections were made at intervals, but at all places examined the sherds were of unmixed Islamic types. Opportunity was taken to talk to many persons who had ranged widely over Arabia and to see collections of objects found both at the sites visited and at many more distant sites. Particular mention must here be made of flint implements found in many areas of the Rub’ al-Khali. Predominating among these artefacts were surface-flaked spearheads and knives which appear to have been found at many points; but a very fine collection of Acheulian-type handaxes was seen, by report collected within a very restricted area in the western Rub’ al-KhaJi, while the same collector possessed also a number of black polished stone celts found at a single site further to the northeast. The two members of the Danish Expedition who were privileged to make this reconnaissance trip wish to record their appreciation of the hospitality so generously offered them, and not least of the superlative organisation which enabled so much to be seen in so short a time. Geoffrey Bibby